2017
DOI: 10.1016/j.scitotenv.2017.01.184
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy and parallel factor analysis as a dissolved organic monitoring tool to assess treatment performance in drinking water trains

Abstract: Fluorescence excitation emission matrix (FEEM) spectroscopy was used to evaluate its applicability as a tool to track dissolved organic matter (DOM) in a drinking water treatment plant (DWTP) that incorporates a conventional line (consisting in ozonation and GAC filtration) and a membrane-based line (consisting in ultrafiltration, reverse osmosis and mineralization) working in parallel. Seven sampling points within the different process stages were characterized monthly during 2014. A global Parallel Factor An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 37 publications
4
17
0
1
Order By: Relevance
“…In a full-scale RO plant study, the "microbial by-product-like" fluorescence signals in the brine were most correlated to fouling (Choi et al, 2014). Vera et al (2017) demonstrated the applicability of EEM-PARAFAC fluorescence signals to track organic fractions throughout conventional and membrane treatment at a full-scale plant. The treatment plants incorporated in the Vera et al (2017) study used river water as influent, and the results identified seasonal variations in the fluorescence measurements and tracked changes in organic matter composition throughout treatment.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a full-scale RO plant study, the "microbial by-product-like" fluorescence signals in the brine were most correlated to fouling (Choi et al, 2014). Vera et al (2017) demonstrated the applicability of EEM-PARAFAC fluorescence signals to track organic fractions throughout conventional and membrane treatment at a full-scale plant. The treatment plants incorporated in the Vera et al (2017) study used river water as influent, and the results identified seasonal variations in the fluorescence measurements and tracked changes in organic matter composition throughout treatment.…”
Section: Introductionmentioning
confidence: 85%
“…As discussed previously, RO permeate samples were excluded from the PARAFAC analysis because they showed almost no fluorescence signal. Vera et al (2017) also found greatly reduced fluorescence signals in the RO effluent because the RO membrane was responsible for removing the largest fraction of organic matter. Additionally, the UF permeate and the second stage RO reject samples showed limited fluorescence signal as well.…”
Section: Case Studymentioning
confidence: 93%
See 1 more Smart Citation
“…Benchtop fluorometers, which are considered to be more sensitive than portable fluorescence sensors, have recently been used to characterize organic matter in drinking water [16][17][18][19] with typically low DOC concentrations (up to <1.0 mg L −1 ). Fluorescence analysis with benchtop fluorometers can be a challenge in field settings due to the poor portability of most benchtop instruments and longer times for spectral acquisition compared to portable sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the complex DOM can be classified by its fluorescent components (fluorophores). However, the quantification of the total amount of organic matter for each fraction is still not solved, indicating that previous calibration should be conducted [19].…”
Section: Introductionmentioning
confidence: 99%